Research methods for criminology and criminal justice - Hartley, Richard D. (Rowman & Littlefield, 2021)
"While written primarily for criminal justice and criminology students, the book offers a general foundation of knowledge that transcends particular topics or subject areas, allowing students to apply research methods and concepts to a multitude of scenarios"--